Bile acids, but not neutral sterols, are tumor promoters in the colon in man and in rodents. - Weisburger, J H (1983)
Analysis of the etiologic factors and relevant mechanisms involved in carcinogenesis leads to a classification of agents involved in the carcinogenic process as genotoxic or epigenetic. Their mode of action is distinct, especially with regard to dose-response effects and reversibility. The genotoxic carcinogens for colon cancer are unknown, but mutagenic components found in fried beef and fish are under study. Epigenetic agents as promoting factors play a major role in the development of cancer of the colon. Specific nutritional elements associated with colon cancer risk are high fat diets, high cholesterol intake, and low fiber intake. The role of micronutrients as modulators and inhibitors needs to be explored. Through metabolic studies in diverse populations and in reliable animal models, it is now clear that dietary fat and cholesterol control the total flow of bile acids in lumen and a high-fat, high-cholesterol diet increases the total of bile acids in the gut. Bile acids but not neutral sterols have promoting effects and are related to colon cancer risk although bile acids by themselves do not act as complete carcinogens. The effect of dietary fiber such as cereal bran is to increase stool bulk which dilutes the concentration of bile acids. Reducing the concentration of bile acids either by lower dietary fat and cholesterol or by increasing dietary fiber may effectively lower the risk for colon cancer.